Analysis of the Legal Regulation of the Internal Control System of Agricultural Organizations - V. A. Mosentseva (Учёт. Анализ. Аудит)
A comprehensive study of the sources of the regulatory framework of the internal control system in Russian agricultural organizations was carried out. The evolutionary and legal approaches to the definition of internal control in these enterprises are compared. The content of the supranational (international), national and local level of the hierarchy of legal acts of the organization of the internal control system for these economic actors is disclosed. The influence of the mechanisms of the digital economy in relation to the field of audit, including Organizing internal control systems in modern enterprises that must cope with new challenges and risks. The tends of agrarian digitalization are indicated, including the fact that the state, through the introduction of digital farm management platforms (digital field, digital flock, digital logistics), will thereby stimulate the agricultural producer; domestic producers of agricultural products are focused on increasing the volume and quality of their products on international markets through the use of modern technologies; centralization and unification of the main directions of the agricultural industry, taking into account the digitization of the economy as a whole.